2009
DOI: 10.1097/acm.0b013e3181a82013
|View full text |Cite
|
Sign up to set email alerts
|

Internal Medicine Clerkship Characteristics Associated With Enhanced Student Examination Performance

Abstract: Certain clerkship characteristics are associated with better student examination performance, the most salient being caring for more patients per day.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 33 publications
0
21
1
Order By: Relevance
“…The small group hours had a p Ͻ 0.05, but the entire model had and R 2 of 0.44, suggesting that these varied effects only explained 44% of the differences in scores. 12 Both of these studies showed a benefit of medical students learning clinical material in small groups, in contrast to the CRQ program, which did not clearly show a difference in scores with smaller groups.…”
Section: Discussionmentioning
confidence: 95%
“…The small group hours had a p Ͻ 0.05, but the entire model had and R 2 of 0.44, suggesting that these varied effects only explained 44% of the differences in scores. 12 Both of these studies showed a benefit of medical students learning clinical material in small groups, in contrast to the CRQ program, which did not clearly show a difference in scores with smaller groups.…”
Section: Discussionmentioning
confidence: 95%
“…In medical education, specifically in internal medicine clerkships, pedagogical approaches, such as more small-group conference hours per week and the use of community-based preceptors, were independently associated with higher USMLE scores on both Step 1 and Step 2. 20 This study also showed that a greater number of clerkship weeks improved performance for students with lower Step 1 examination scores, whereas continuity of the attending physician for 4 weeks vs 2 weeks significantly improved the change in examination scores from Step 1 to Step 2 regardless of a high or low baseline Step 1 score. 20 A study that compared the performance of 27 third-year medical students in a longitudinal integrated clerkship design with 45 students in a traditional block design reported statistically better performance on an objective structured clinical examination and 3 of 6 standardized knowledge assessments.…”
Section: Discussionmentioning
confidence: 61%
“…20 This study also showed that a greater number of clerkship weeks improved performance for students with lower Step 1 examination scores, whereas continuity of the attending physician for 4 weeks vs 2 weeks significantly improved the change in examination scores from Step 1 to Step 2 regardless of a high or low baseline Step 1 score. 20 A study that compared the performance of 27 third-year medical students in a longitudinal integrated clerkship design with 45 students in a traditional block design reported statistically better performance on an objective structured clinical examination and 3 of 6 standardized knowledge assessments. 21 In the same study, which also measured medical student perceptions related to continuity of supervision, students in the integrated design reported significantly more feedback on clinical performance and receiving 1-on-1 mentoring.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Despite this difference, the results show that supervising clinicians agree that trained medical students are sufficiently competent to carry out supervised TCs with real patients. Regarding the appreciation for the TC, earlier studies have also shown that students appreciate supervised interaction with real patients (Murray et al 2001; Griffith et al 2009). Furthermore, TCs with real patients constitute an optimal form of context learning, which is an effective learning method (Vollebregt et al 2006; Richir et al 2008; Charlin et al 2007; Mann 2002; Schmidt and Rikers 2007; Chastonay et al 1996).…”
Section: Discussionmentioning
confidence: 98%